2023
DOI: 10.3390/molecules28052090
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Molybdenum in Hydrogen Peroxide: A Thermodynamic, Kinetic and Microscopic Study of a Green Process for 99mTc Production

Abstract: 99mTc-based radiopharmaceuticals are the most commonly used medical radioactive tracers in nuclear medicine for diagnostic imaging. Due to the expected global shortage of 99Mo, the parent radionuclide from which 99mTc is produced, new production methods should be developed. The SORGENTINA-RF (SRF) project aims at developing a prototypical medium-intensity D-T 14-MeV fusion neutron source specifically designed for production of medical radioisotopes with a focus on 99Mo. The scope of this work was to develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Experimental observations have shown that molybdenum is more reactive than tungsten, i.e., with the same mass, volume of peroxide and other conditions, the former dissolves completely faster than the latter and, in both cases, the reaction initially is slow for a short induction time, which depends on the temperature. However, once the reaction starts, it proceeds rapidly with a large development of heat (they are highly exothermic) and the formation of a large quantity of bubbles, mainly oxygen [34]. This is possibly due to the fact that the surfaces of metallic pieces are covered by a very thin layer of oxide with intermediate valence, such as MoO 2 , and that it acts as a passivation layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental observations have shown that molybdenum is more reactive than tungsten, i.e., with the same mass, volume of peroxide and other conditions, the former dissolves completely faster than the latter and, in both cases, the reaction initially is slow for a short induction time, which depends on the temperature. However, once the reaction starts, it proceeds rapidly with a large development of heat (they are highly exothermic) and the formation of a large quantity of bubbles, mainly oxygen [34]. This is possibly due to the fact that the surfaces of metallic pieces are covered by a very thin layer of oxide with intermediate valence, such as MoO 2 , and that it acts as a passivation layer.…”
Section: Resultsmentioning
confidence: 99%
“…Molybdenum and tungsten have many similar chemical properties, including their reactivity with respect to concentrated H 2 O 2 solutions [ 34 ]. This also suggests that a solid solution can form.…”
Section: Introductionmentioning
confidence: 99%
“…Crystals of Ag 2 MoO 4 were prepared by the precipitation route by mixing liquid solution of AgNO 3 (Carlo Erba Reagents, Milano, Italy, purity 99.8%) and Na 2 MoO 4 under different conditions. In turn, Na 2 MoO 4 was prepared from metallic Mo (Luoyang Combat Tungsten & Molybdenum Material Co., Ltd. (Luoyang, China), purity = 99.9%) by reaction with H 2 O 2 35% (Carlo Erba Reagents), according to [14,15]. Solid Molybdenum reacts quickly with hydrogen peroxide, leading to a clear solution of molybdic acid (H 2 MoO 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The general description of the project and the main activities can be found in further detail in [3] while a set of specific studies is presented in [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%